The Effectiveness of Social Media Marketing on Tudung Saji MSME Products in Maholo Village - Moh. Rezky Saputra; Ponirin; Syamsul Bahri; Asriadi (PT. Global World Scientific, 2024)
Tudung Saji MSME is a micro business that was established in 2018 in Maholo Village, East Lore District, Poso Regency. This activity aims to improve the skills, understanding, and capacity of MSME actors in utilizing social media as a means of product promotion. The focus of the training is directed at increasing digital competence and online marketing, in response to changes in consumer behavior that are increasingly dependent on digital platforms. The method used is a descriptive qualitative approach, with direct implementation at MSME locations. The results of the activity show that MSME players are able to create and manage WhatsApp Business accounts as promotional media, as well as understand the basics of digital marketing strategies. This activity is expected to be the first step in developing the digital ecosystem of MSMEs in rural areas, while increasing the competitiveness of local products in a wider market.